Tecumseh, Shawnee war chief - Fleischer, Jane.; Frenck, Hal (Mahwah, NJ : Troll, 1979)
Presents the life of the Shawnee Indian who tried to unite all the American Indian tribes against invasion by the white man.
School Library Journal
Booklist
4.2
3-6
Keywords: Tecumseh, Shawnee Chief, -- 1768-1813.; Shawnee Indians -- Biography; Indians of North America -- Biography; Tecumseh, Shawnee Chief, -- 1768-1813; Shawnee Indians -- Biography; Indians of North America -- Biography